2013
DOI: 10.1111/cobi.12186
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rotational Shepherding on Demographic and Genetic Connectivity of Calcareous Grassland Plants

Abstract: Response to habitat fragmentation may not be generalized among species, in particular for plant communities with a variety of dispersal traits. Calcareous grasslands are one of the most species-rich habitats in Central Europe, but abandonment of traditional management has caused a dramatic decline of calcareous grassland species. In the Southern Franconian Alb in Germany, reintroduction of rotational shepherding in previously abandoned grasslands has restored species diversity, and it has been suggested that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
35
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 47 publications
6
35
1
Order By: Relevance
“…Population genetic diversity in patches grazed by sheep exhibits higher levels of genetic diversity compared with ungrazed patches (Rico et al . ). Average inbreeding F IS in D. carthusianorum was rather low ( F IS = 0.095), but contrary to our expectation, small ungrazed populations showed lowest F IS coefficients, which were significantly lower than those of small populations of grazed patches.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Population genetic diversity in patches grazed by sheep exhibits higher levels of genetic diversity compared with ungrazed patches (Rico et al . ). Average inbreeding F IS in D. carthusianorum was rather low ( F IS = 0.095), but contrary to our expectation, small ungrazed populations showed lowest F IS coefficients, which were significantly lower than those of small populations of grazed patches.…”
Section: Discussionmentioning
confidence: 97%
“…A previous analysis in D. carthusianorum in this study area suggested that both patch occupancy and genetic diversity are associated with rotational shepherding (Rico et al . ).…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…However, it has recently been reported that the genetic diversity of the grassland species Succisa pratensis depends on the historical landscape structure of the habitat [15], which supports the results of our study. Moreover, it has been shown that the genetic diversity of Dianthus carthusianorum depends on patch connectivity by shepherding [61] and that population disconnection can create a genetic bottleneck, even in the absence of a demographic collapse [62], which underlines the importance of historical gene flow for the level of current genetic diversity.…”
Section: Discussionmentioning
confidence: 99%